Acquired subglottic cysts in children: A rare and challenging clinical entity. A systematic review. (January 2021) - Soloperto, Davide; Spinnato, Federica; Di Gioia, Stefano; Di Maro, Flavia; Pinter, Patrick; Bisceglia, Alfonso; Marchioni, Daniele
Abstract: Introduction: Subglottic cysts (SGCs) are a rare cause of laryngeal stenosis that mainly seem to affect preterm infants with an intubation history. Purpose: To review the related literature and compare different management protocols for patients presenting SGCs, as well as briefly report our clinical case treated at Verona University Hospital by Pediatric Airways Team. Methods: The articles resulting from a PubMed and MEDLINE search were analysed and selected using previously established criteria. A systematic review of the selected papers was conducted following PRISMA guidelines. Results: The search yielded 571 related articles; cross-checking of articles led to the identification and exclusion of 239 duplicates. The remaining 332 papers were screened according to previously established eligibility criteria. The final number of selected articles was 13. Conclusions: Well-planned teamwork, with active collaboration between the ENT specialists, pediatricians and anesthesiologists, is the key to achieve multidisciplinary management of patients diagnosed with SGCs. Long-term follow-up is crucial considering the high recurrence rate of this disease.